(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
It is said that the newborn a clinic for pneumonia in babies with a number of features and only with a hearth and breathing without signs of systemic inflammation can be manifested with a violation.Some researchers fever and tachypnea presence in newborns an important diagnostic sign of pneumonia they believe that. Pneumonia is inflammation of the lungs, an infectious disease of the lungs, an independent disease or a complication of other diseases.